The abandoned space: a collection of dreams and fantasies - Leow, Puay Tin *; Teh, Mark * (Sunway University. Dept. of Performance & Media, 2007)
Devised theatre performance based on the theme of dreams and fantasies. Contents: Library. - The perfect ride. - Good listeners. - Grace vs. Grace. - Dreams and science. - Pyro. - My perfect companion. - A special place. - Witch. - Rugby captain pirate. - Dreams and freud. - Dreams and anthropology. - Perfect family. - Petrified. - Night becomes morning. - Ummi's fantasy. - Dreams and health. - Dreams and Carl Jung. - The mermaid goddess. - New York city. - The meeting. - Legend. - Dreams and folklore. - Lagoon on fire. - Meeting a special someone.